Early surgical outcomes and oncological results of robot‐assisted partial nephrectomy: a multicentre study. (18th January 2017) - Veeratterapillay, Rajan; Addla, Sanjai K.; Jelley, Clare; Bailie, John; Rix, David; Bromage, Steve; Oakley, Neil; Weston, Robin; Soomro, Naeem A.
Abstract : Objective: To describe a multicentre experience of robot‐assisted partial nephrectomy (RAPN) in northern England, with focus on early surgical outcomes and oncological results. Patients and Methods: All consecutive patients undergoing RAPN at four tertiary referral centres in northern England in the period 2012–2015 were included for analysis. RAPN was performed via a transperitoneal approach using a standardized technique. Prospective data collection was performed to capture preoperative characteristics (including R.E.N.A.L. nephrometry score), and peri‐operative and postoperative data, including renal function. Correlations between warm ischaemia time (WIT), positive surgical margin (PSM) rate, complication rates, R.E.N.A.L. nephrometry scores and learning curve were assessed using univariate and multivariate analyses. Results: A total of 250 patients (mean age 58.1 ± 13 years, mean ± sd body mass index 27.3 ± 7 kg/m 2 ) were included, with a median (range) follow‐up of 12 (3–36) months. The mean ± sd tumour size was 30.6 ± 10 mm, mean R.E.N.A.L. nephrometry score was 6.1 ± 2 and 55% of tumours were left‐sided. Mean ± sd operating console time was 141 ± 38 min, WIT 16.7 ± 8 min and estimated blood loss 205 ± 145 mL. There were five conversions (2%) to open/radical nephrectomy. The overall complication rate was 16.4% (Clavien I, 1.6%; Clavien II, 8.8%; Clavien III, 6%; Clavien IV/V; 0%). Pathologically, 82.4% of tumours were malignant and the overall PSM rate was 7.3%. The mean ± sd preoperative and immediate postoperative estimated glomerular filtration rates were 92.8 ± 27 and 80.8 ± 27 mL/min/1.73 m 2, respectively ( P = 0.001). In all, 66% of patients remained in the same chronic kidney disease category postoperatively, and none of the patients required dialysis during the study period. 'Trifecta' (defined as WIT < 25 min, negative surgical margin status and no peri‐operative complications) was achieved in 68.4% of patients overall, but improved with surgeon experience. PSM status and long WIT were significantly associated with early learning curve. Conclusion: This is the largest multicentre RAPN study in the UK. Initial results show that RAPN is safe and can be performed with minimal morbidity. Early oncological outcomes and renal function preservation data are encouraging.